Does sites of recurrence impact survival in secondary cytoreduction surgery for recurrent epithelial ovarian cancer?. (17th August 2020) - Kumar, Satyam; Srinivasan, Ananth; Phillips, Andrew; Madhupriya, R; Pascoe, Jennifer; Nevin, James; Elattar, Ahmed; Balega, Janos; Cummins, Carole; Sundar, Sudha; Kehoe, Sean T.; Singh, Kavita
Abstract: Outcomes of secondary cytoreduction surgery (SCS) were evaluated for morbidity, progression free survival (PFS) and overall survival (OS) and factors influencing results were explored. Retrospective analysis of all cases of SCS for epithelial ovarian cancer (EOC) was performed from October 2010 to December 2017. 62 patients were prospectively identified as candidates for SCS and 57 underwent SCS. 20(35%) patients required bowel resection/s, 24(42%) had nodal resections and 11(19%) had extensive upper abdominal surgery. 51(89%) achieved complete cytoreduction. After a median follow-up of 30 months (range 9–95 months), median PFS was 32 months (CI 17–76 months) and median OS has not reached. Seventeen patients have died and 32 have progressed. Three patients had Clavien-Dindo grade-3 and two had grade-4 morbidity. Patients who had multi-site recurrence had shorter median PFS ( p  = 0.04) and patients who required bowel resections had lower median OS ( p  = 0.009) compared to rest of the cohort. IMPACT STATEMENT: What is already known on this subject? Retrospective studies have confirmed survival advantage for recurrence in epithelial ovarian cancer and recommend SCS for carefully selected patients. This finding is being evaluated in randomised control trials currently. What do the results of this study add? This study presents excellent results for survival outcomes after SCS and highlights importance of careful selection of patients with a goal to achieve complete cytoreduction. In addition, for the first time in literature, this study also explores various factors that may influence results and finds that there are no differences in survival outcomes whether these patients had early stage or advanced stage disease earlier. Patients who have multisite recurrence tend to have shorter PFS but no difference were noted for overall survival. Patients who have recurrence in bowels necessitating resection/s have a shorter median OS compared to rest of cohorts, however, still achieving a good survival time. What are the implications of these findings for clinical practice and/or further research? These findings will raise awareness for the clinicians and patients while discussing surgical outcomes and would set an achievable standard to improve cancer services. The pattern of recurrence and associated outcomes also point towards difference in biological nature of recurrent disease and could provide an opportunity for scientists to study the biological makeup of these recurrent tumours.